Influence of feed additive from peat on morphological and biochemical blood profile of piglets - Yefimov, Valentyn; Єфімов, Валентин Геннадійович; Kostiushkevych, Kostiantyn; Костюшкевич, Костянтин Леонідович; Rakytianskyi, Vitalii; Ракитянський, Віталій Миколайович (Lietuvos Veterinarijos Akademija, 2017)
The aim of our study was to establish the influence of feed additive based on peat on physiological and biochemical parameters of blood of piglets in the suckling and early post-weaning period. For this purpose, the control and the experimental groups of piglets were formed. The experimental animals were additionally getting feed additive from the 3rd to the 42nd day of life. Blood was sampled at the end of the experimental period. At the end of the study, the feed additive was found to decrease the signs typical to the stress syndrome. It increases the basophiles and eosinophiles count in blood, as well as decreases the neutrophils count in blood by 26.7 % (P<0.05). Biochemical changes indicate an increase in the level of albumin by 9.0 % (P<0.05) and a decrease in glucose concentration by 17.4 % (P<0.05). Thus, the use of a feed additive for piglets leads to greater adaptive capacity of piglets to the stress associated with their weaning and the transition to combifodder consumption. Метою нашого дослідження було встановити вплив кормової добавки на основі торфу («Торвет») на фізіологічні та біохімічні показники крові поросят в підсисний і ранній післявідлучний період. Для цього було сформовано контрольну і експериментальну групи поросят. Експериментальні тварини додатково отримували кормову добавку з 3-го по 42-й день життя. Кров відбирали в кінці експериментального періоду. В результаті досліджень було встановлено, що кормова добавка зменшує ознаки, характерні для синдрому стресу. Вона збільшує кількість базофілів і еозинофілів в крові, а також зменшує кількість нейтрофілів на 26,7% (р <0,05). Біохімічні зміни вказують на збільшення рівня альбуміну на 9,0% (р <0,05) і зниження концентрації глюкози на 17,4% (р <0,05). Таким чином, використання кормової добавки для поросят призводить до більшої адаптаційної здатності поросят до стресу, пов'язаного з їх відлученням і переходом до споживання комбікормів.
Вплив кормової добавки з торфу на морфологічний та біохімічний профіль крові поросят
Keywords: blood morphology and biochemistry; морфологія і біохімія крові; piglets; поросята; weaning; відлучення; peat additive; торф’яна добавка